PENGARUH MEDIA PEMBELAJARAN POP-UP BOOK TERHADAP MINAT BELAJAR PESERTA DIDIK PADA MATERI FLORA DAN FAUNADI PEMBELAJARAN IPAS KELAS V - Musdhalifah, Nike; Sulistyowati, Ida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
One reason kids don't care much about learning is because there isn't much variety in the learning process, which is the premise of this study. Inadequate resources, such as social studies learning media, contribute to students' lack of motivation to study, among other factors. The goal of this research is to find out how fifth graders' interest in learning about flora and fauna is affected by using pop-up books as a learning tool in social studies class. Quantitative studies of a quasi-experimental design are what this study is all about. Fifth graders participated in the study by splitting into two groups: one that used Pop-Up Book media for experimentation and another that used more traditional teaching strategies. Questionnaires were used to gather data. We anticipate that the study's findings will shed light on how well Pop-Up Book media piques students' interests in learning and offer suggestions on how to include interactive learning materials into classroom instruction. After using Pop-Up Book, the experimental class outperformed the control class on the post-test, indicating that pupils' interest in learning had increased. Results from post-lesson surveys and subsequent analysis using independent sample tests demonstrated a statistically significant effect of Pop-Up Books on students' motivation to study.